2014
DOI: 10.1039/c4cc05909c
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent maleimide functionalization of gold nanoparticlesviacopper-free click chemistry

Abstract: A single maleimide was installed onto the self-assembled monolayer of gold nanoparticles by copper-free click chemistry. Simple covalent biofunctionalisation is demonstrated by coupling fibroblast growth factor 2 and an oligosaccharide in a 1 : 1 stoichiometry by thiol-Michael addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…These can be coupled flexible with various molecules carrying different targeted functionalities . Other modification studies using TEMA have been reported for different surfaces and particles including glass and polymer surfaces, salmon calcitonin (sCT), hydrogels, AuNPs, magnetic nanoparticles (Fe 3 O 4 ), porous cellulose nanocrystals/poly(vinyl alcohol) nanocomposite films on glass, porous polymeric monolith, and a mixed macrodiol polyurethane and tantalum …”
Section: Introductionmentioning
confidence: 99%
“…These can be coupled flexible with various molecules carrying different targeted functionalities . Other modification studies using TEMA have been reported for different surfaces and particles including glass and polymer surfaces, salmon calcitonin (sCT), hydrogels, AuNPs, magnetic nanoparticles (Fe 3 O 4 ), porous cellulose nanocrystals/poly(vinyl alcohol) nanocomposite films on glass, porous polymeric monolith, and a mixed macrodiol polyurethane and tantalum …”
Section: Introductionmentioning
confidence: 99%
“…At higher mole % the number of FluPep ligands per nanoparticle will increase. It is interesting to note that not all gold nanoparticles were observed to bind to the CM Sepharose resin at higher mole % of FluPep ligand, something that has been observed previously with other functional peptides (Nieves et al, 2014, Paramelle et al, 2015. Nonetheless, this straightforward purification of the functionalised gold nanoparticles means that the effects on influenza virus infectivity of mono-versus plurifunctionalisation can be determined.…”
Section: Purification Of Flupep Functionalised Gold Nanoparticlesmentioning
confidence: 71%
“…To functionalise the nanoparticles, the peptide FluPep ligand was included in the ligand mix, its mole % in relation to the matrix ligand reflects its grafting density on the gold nanoparticles (Levy et al, 2006, Duchesne et al, 2008a, Duchesne et al, 2012, Paramelle et al, 2015, Nieves et al, 2014. This can be determined by chromatography targeting specifically the grafted function, which also provides a means to purify the functionalised gold nanoparticles from those not Mix matrix gold nanoparticles did not to CM Sepharose nor to DEAE Sepharose ( Fig.…”
Section: Purification Of Flupep Functionalised Gold Nanoparticlesmentioning
confidence: 99%
“…The liberated maleimide groups were subsequently used in a Michael addition reaction with cysteine. More recently, an elegant combination of metal‐free click reactions was reported by Fernig and co‐workers, who used the thiol‐Michael addition for the functionalization of maleimide‐functionalized Au NPs with dithiothreitol (DTT) . Initially, the maleimide‐functionalized Au NPs were prepared by a SPAAC reaction between DIBO‐terminated maleimides and azide‐functionalized Au NPs, and the subsequent thiol‐Michael addition with DTT yielded thiol‐functionalized nanoparticles, which were again used to react with maleimide‐functionalized heparin‐derived oligosaccharides through a second thiol‐Michael addition.…”
Section: Thiol‐michael Addition Reactionsmentioning
confidence: 99%